(untitled) (Fiep Bulletin - online, 2014)
The sedentariness is related to style of life with little physical activity. This can be mensured through the energy expense or great expense caloric that an individual needs to carry through its activities of work and domestic, leisure and locomotion. If this great expense caloric will be inferior the 500kcal per week this individual is classified as sadentary(S) and if individual accumulate a great expense 1.000 weekly caloric of kcal, it is classified moderately active (Ma). Objective: To analyze the association between the level of physical activity and the style of life of inhabitants of the west zone of Rio De Janeiro. Methodology: The present study was characterized as descriptive according to Thomas Nelson (2006), the sample was composed by 38 individuals, of a condominium in the Barra da Tijuca of the city of Rio De Janeiro, being 13 of male gender and 25 of the female gender. It was used the questionnaires of the STYLE OF LIFE (NAHAS, 2006) and the IPAQ (International Questionnaire of Physical Activity) in the short version. Results: The data had demonstrated a greater percentile of active individuals in the studied group. In accordance with the analyzed components, in the one that refers to Nutrition component in such a way men how much women had left question blank, where if it could no longer observe that in both genders do not have the habit of inclusion of fruits and vegetable in its daily alimentation, component Physical Activity although not to have a practical habit of of physical activity at least 30 minutes at least 3 times in the week, all opt to going up stairs when going up of elevator, in relation to the Relationship both genders had gotten maximum value for each question. In that it refers to to the Preventive Behavior had a positive point where habits as to smoke and to ingest alcoholic drinks, they are not part of the style of life of these evaluated, however the individuals of the male gender do not possess the habit of control of arterial pressure and cholesterol levels what it is a very preoccupying factor, being able to propitiate to the development of cardiovascular problems, since it has a deficit found in the component physical activity. In relation to the control of stress the results had been considered satisfactory, therefore all look for to take a balanced life.